Effects of a novel NADPH oxidase inhibitor (S42909) on wound healing in an experimental ischemic excisional skin model. Issue 2 (29th December 2016) - Sotomayor, Sandra; Pascual, Gemma; Blanc‐Guillemaud, Vanessa; Mesa‐Ciller, Claudia; García‐Honduvilla, Natalio; Cifuentes, Alberto; Buján, Julia
Abstract: Chronic wounds are a serious healthcare problem. As non‐healing wounds involve continuous pathologic inflammatory stage, research is focused on anti‐inflammatory treatments. Our objective was to analyze the effect of S42909, a potent NADPH oxidase inhibitor activity, with vascular anti‐inflammatory properties. An ischemic rabbit ear ulcer model (24 New Zealand white rabbits) was used to evaluate the reepithelialization/contraction areas, anti‐/pro‐inflammatory cytokines mRNA (TGF‐β1/IL‐10/IFN‐γ/VEGF) by qRT‐PCR, collagen I/III deposition, and neovascularization (TGF‐β1/VEGF) by morphological and immunohistochemical analyses. Three different doses were administered by gavage for 2 weeks: 10 and 30 mg/kg/d in self‐microemulsion drug delivery system (SMEDDS) and 100 mg/kg/d in arabic gum. Each vehicle was used as control. No signs of infection or necrosis were found. Reepithelialization was almost complete whatever the groups reaching 95% at the dose of 100 mg/kg. Wound contraction was significantly reduced in all S42909‐treated groups. A significant increase in anti‐inflammatory cytokines TGF‐β1 mRNA and IL‐10 mRNA was observed at the dose of 100 and 30 mg/kg/d, respectively. No changes were observed in pro‐inflammatory factors INF‐γ and VEGF mRNA. Ischemic skin wound areas had scarce expression of collagen I/III and showed rich glycosaminoglycans content. Treatment increased the collagen deposition and TGF‐β1 protein expression and decreased glycosaminoglycan content dose dependently; however, no effect in VEGF was appreciated. Therefore, our results indicate that S42909 improved healing process by dampening excessive inflammation and facilitating collagen deposition without wound contraction phenomena. S42909 might be a promising therapy to treat chronic wounds as venous leg ulcers.